Akurasi Keputusan dalam Penentuan Guru Berprestasi Dengan Menggunakan Metode Simple Additive Weighting (Studi Kasus Sekolah Menengah Kejuruan Muhammadiyah Batam) - Wahyudi, Wahyudi; Santony, Julius; Nurcahyo, Gunadi Widi (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to obtain decision accuracy in determining teacher achievement using the Simple Additive Weighting method. Problems in Batam Muhammadiyah Vocational High School in determining the achievement of teachers using assessment criteria with the weight of educational qualifications, discipline, neatness, character, personality and teaching methods. The ranking process stage determines the alternatives of selected teacher achievement using the input of criteria weights. The results of this study get an accuracy rate of 80% with an accurate, fast, objective value. In the future, this research will be used as a new standard in determining teacher achievement.